2018
DOI: 10.3892/ijmm.2018.3697
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‑17‑5p protects against high glucose‑induced endothelial cell injury by targeting E2F1‑mediated suppression of autophagy and promotion of apoptosis

Abstract: E2 promoter binding factor 1 (E2F1) has been reported to have an important regulatory role in cell survival during hyperglycemic conditions; however, the mechanisms remain to be fully elucidated. Bioinformatics analyses have suggested that microRNA (miR)‑17‑5p targets the 3'untranslated region (3'UTR) of E2F1. The aim of the present study was to characterize the protective effect of miR‑17‑5p/E2F1 on human umbilical vein endothelial cells (HUVECs) under high glucose (HG) conditions, to confirm the regulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Autophagy is a process in which cells encapsulate their own proteins or damaged organelles in vesicles that are then fused with lysosomes to form autophagy lysosomes and the contents are degraded (32). A study has demonstrated that autophagy serves important roles in the survival of vascular endothelial cells (33). The MIF1 gene regulates the permeability of vascular endothelial cells by inducing autophagy (34), while the SIRT1 gene regulates the degradation of LDL in HUVECs via the autophagy-lysosome pathway (35).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a process in which cells encapsulate their own proteins or damaged organelles in vesicles that are then fused with lysosomes to form autophagy lysosomes and the contents are degraded (32). A study has demonstrated that autophagy serves important roles in the survival of vascular endothelial cells (33). The MIF1 gene regulates the permeability of vascular endothelial cells by inducing autophagy (34), while the SIRT1 gene regulates the degradation of LDL in HUVECs via the autophagy-lysosome pathway (35).…”
Section: Discussionmentioning
confidence: 99%
“…miR‐24, miR‐106a and miR‐130a‐3p alleviate hyperglycemia‐induced podoplanin cellular inflammation and apoptosis in diabetic nephropathy 116–118 . miR‐17‐5p and miR‐24 protect against hyperglycemia‐induced endothelial cell damage and enhance autophagy in DM‐associated endothelial dysfunction 119,120 . As these miRNAs are significantly downregulated in obesity, they could indicate imminent complications of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 is involved in cell cycle regulation, apoptosis signal transduction, cell growth, metastasis, autophagy, and other processes ( Yuan et al, 2018 ). The study demonstrated the specific biological function of E2F1 in the progression and related complications of DM.…”
Section: Discussionmentioning
confidence: 99%